Improving Children’s Understanding of Early Sex Education through Modified Puppet - Syaiputra Wahyuda Meisa Diningrat; Muksin Muksin; Indi Ari Pratiwi (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
Educators have increasingly provided teaching and learning practices to teach children’s understanding of early sex education. In accordance with the inappropriate of the teaching practices, the current study examined the effectiveness of utilization modified puppet within play-based learning approach. A quasi-experimental research design was employed with two classes in a private kindergarten in Galis subdistrict. This study evolved 61 children, aged 5-6 years. During four weeks, the experimental class received modified puppet in their learning activity and the control class condition received conventional learning. Before, and after, the four weeks modified puppet intervention, measures of children’s understanding of early sex education were administered to all groups. The findings showed that the children’s understanding of early sex education who taught by the modified puppet outperformed children who received conventional method. However, the findings need to be explored with an extended to different learning outcomes that involve larger groups of participants.